An essay on Darwin's theory and Bergson's creative evolution in the era of neuroQuantology - Güntekin, Bahar; BAŞAR, EROL (Anka Publisher, 116-11 Sok No.10 K 2 D 2, Bornova, Izmir 35050, Turkey, 2009)
Charles Darwins's evolution theory was surveyed and analyzed by Henri Bergson in his book "Evolution Creatrice" (1907). Bergson described the importance of "intuition" and "cognitive processes" during evolution. The present essay describes the importance of entropy changes during evolution of species and development of cognition and intuition. The importance of Bergson's philosophy in modern sciences is globally explained.
Keywords: Darwin; Bergson; Evolution; Neuroquantology; Intuition; Entropy; Gill-Withdrawal Reflex; Brain; Aplysia; Oscillations; Habituation; Potentials; Coherence; System; Rhythm; View; Evrim; Sezgi; Entropi; Solungaç-Geri Çekilme Refleksi; Beyin; Salınımlar; Alışma; Potansiyeller; Uyum; Ritim; Görünüm; Sistem